APPLICATION OF IAS 19 EMPLOYEE BENEFITS - PARTICIPATION OF PROFITS IN PERU - Rodríguez Chávez, Agustín (2012)
In January 2011, the Accounting Standards Board (Consejo Normativo de Contabilidad) recognized profit sharing of employees on tax bases in accordance with IAS 19 Employee Benefits and not by analogy with IAS12 – Tax Income or IAS 37 Provisions, Contingent Liabilities and Contingent Assets. This is based on consultations made to the International Financial Reporting Interpretation Committee – IFRIC, which at its meeting on November 4, 2010, concluded, in respect to the accounting of profit-sharing of employees, which was calculated in accordance with tax legislation, that the recognition of the profitsharing of employees will be in accordance with the provision of the International Accounting Standard 19, Employee’s Benefits, and this is only for the compensation of services provided during the year. Therefore, not should be recorded a deferred tax assets or a deferred tax liability as is required in IAS 12, Income Taxes. This legal disposition requires companies to make changes in its account practices and policies in order to recognize the profit sharing and compliance on the provisions of this rule. However, there is a lack of precision on the effects of management, a lack of information on compliance with tax standards and a lack of analysis on the formulation of financial statements. As a result of this, costing processes, accounting records, determination of profits or loss and financial measurements will be affected by the changes in the structure of the financial statements. We have seen at year end of 2011 and on the following months that many companies have failed in the implementation of the standard or have only partially fulfilled it, and it’s our aim to make the necessary analysis, and to explain the reason for this breach and submit a proposal for practices and policies for compliance. We hope that this contribution allows a better understanding of the scope of this rule in our country and that business community and accounting count with an option of application.